Administrative staff training and development policy implementation - Baharom, Aniah (2008)
It has been emphasised by HRD advocates that an organisation’s human resource is no more only a resource, but a capital with the potential to determine the success and development of the organisation. This claim is further supported by numerous research carried out in the HRD field. The realisation of the importance of human resource or human capital on nation building and organisational development has prompted the conception of various national and organisational mechanisms designed to develop human capital in the country for the public and private sectors. In the wake of the approaching deadline for the realisation of Vision 2020 and the rolling out of the Ninth Malaysian Plan, the public service delivery at the state and federal government has again been subjected to public scrutiny. Hence, this study was conducted as an attempt to contribute and shed some light on efforts made by public universities in Malaysia to develop their administrative staff with the assurance that this will result in better service delivery. This study investigated the current state of implementing administrative staff training and development policies in Malaysian Public Universities. 232 university administrators from 14 public universities were surveyed on issues related to the implementation of training and development policy for administrative staff within the university population. The factors included in the study were the availability of resources needed for implementation, environmental conditions surrounding implementation and the dispositions of implementers. Significant findings related to policy performance at the departmental and staff level are also reported.